Kajian Literatur Manajemen Privasi dalam Konteks Hubungan Keluarga di Facebook - Alice Raga Dewi (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2023)
The rapid development of technology makes social media an important part of the communication process. Facebook as one of the most popular social media and has many users encourages the emergence of privacy disturbances. As the number of families using Facebook increases, the risk of privacy disclosure also becomes more open in the public sphere. The management of personal data and information on social media has triggered privacy disturbances. The research team used a qualitative methodology with a literature review method to examine privacy management using the theory of Communication Privacy Management (CPM) in the family context on Facebook Social Media. The results of the study show that as owners of individual information, they apply privacy controls through privacy rules and restrictions as a way to decide what to disclose and hide on Facebook. Privacy disclosure decisions are influenced by the quality of family relationships and topics of discussion. Individuals will apply personal boundaries to information related to sex and HIV disease. Privacy controls carried out by individuals in the context of family relationships on Facebook are carried out to avoid turbulence.ABSTRAK Perkembangan teknologi yang kian pesat menjadikan media sosial bagian penting dalam proses komunikasi. Facebook sebagai salah satu media sosial yang populer dan memiliki banyak pengguna mendorong munculnya gangguan privasi. Seiring bertambahnya jumlah keluarga yang menggunakan Facebook, risiko pengungkapan privasi juga kian terbuka di ruang publik. Pengelolaan data dan informasi pribadi di media sosial telah memicu gangguan privasi. Tim peneliti menggunakan metodologi kualitatif dengan metode kajian literatur untuk menelaah manajemen privasi dengan menggunakaan teori Communication Privacy Management (CPM) dalam konteks keluarga di Media Sosial Facebook. Hasil penelitian menunjukan bahwa sebagai pemilik informasi individu menerapkan kontrol privasi melalui aturan dan batasan privasi sebagai cara untuk memutuskan apa yang akan diungkapkan dan disembunyikan di Facebook. Keputusan pengungkapan privasi dipengaruhi oleh kualitas hubungan dalam keluarga dan topik bahasan. Individu akan menerapkan batasan pribadi untuk informasi yang terkait seks dan penyakit HIV. Kontrol privasi yang dilakukan oleh individu dalam konteks hubungan keluarga di Facebook dilakukan untuk menghindari terjadinya turbulensi.